2017
DOI: 10.1002/jcb.25720
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of I91T Sod2 Polymorphism of Saccharomyces cerevisiae

Abstract: The mitochondrial antioxidant enzyme Mn-Superoxide Dismutase (Sod2) is essential for mammalian survival. I82T mutation in human Sod2 has been linked to a wide variety of diseases, including Alzheimer's and Parkinson's diseases as well as some types of cancers. Yeast wild-type (WT) Sod2 and the mutant Sod2 I91T, which corresponds to the human mutant Sod2 I82T, were cloned in sod2Δ strain. Residue I82 is conserved among a variety of species, showing that it has a biological importance. To assess the functionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The plates had been incubated at 28 °C for 72 h, and the colonies were counted. Viability was determined before and after growth (4749). Malondialdehyde, a final product of lipid peroxidation, was measured by thiobarbituric acid reactive species (TBARS) method (50).…”
Section: Methodsmentioning
confidence: 99%
“…The plates had been incubated at 28 °C for 72 h, and the colonies were counted. Viability was determined before and after growth (4749). Malondialdehyde, a final product of lipid peroxidation, was measured by thiobarbituric acid reactive species (TBARS) method (50).…”
Section: Methodsmentioning
confidence: 99%
“…Millions of people are subjected to As poisoning from contaminated water and food resources (Li et al, 2015). Arsenicals exert toxicity by inactivating up to 200 enzymes, among which superoxide dismutase (SOD) is considered as the first line of mitochondrial defense against oxidative damage (De Carvalho et al, 2017). As toxicity is positively associated with DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the central role of SOD3 in oxidative stress effects, the complete SOD3 structure remains unresolved. 15 In this study, structural modeling, molecular dynamics (MD) simulations, and SNP functional predictions were applied, following the methodology previously established by our group 9,11,12 for an in silico analysis of the SOD3 protein and its natural variants. We aimed to conduct a thorough analysis of the protein structures, as well as the possible effects of structural changes in disease development.…”
Section: Introductionmentioning
confidence: 99%
“…This is believed to impair the subcellular localization of SOD2 . The A16V polymorphism has been associated with the development of Alzheimer's and Parkinson's diseases . Studies have shown that the I82T mutation decreases the SOD2 activity .…”
Section: Introductionmentioning
confidence: 99%